Dampak Dilakukannya Mitigasi Bencana Banjir Oleh Badan Penanggulangan Bencana Daerah Kabupaten Lima Puluh Kota di Nagari Taram - Zahari Basri; Zikri Alhadi (Jurnal Teori dan Riset Administrasi Publik, 2021)
This study aims to determine the flood disaster mitigation in Nagari Taram which is carried out by the regional disaster management district of Lima puluh kota. There are still frequent floods in Nagari Taram, especially during the rainy season, although there has been mitigation carried out by the BPBD district of Lima puluh kota. Mitigation is carried out by normalizing the Batang Sinamar river, building gabions, enlarging river flow and installing grass thickets to retain river cliffs. This research method is a qualitative method with a descriptive type. The location of this research is in the office of the district disaster management agency in fifty cities, the office of public works and spatial planning as well as the office of the Taram nagari guardian. Collecting data using observational interviews and documentation studies. Research information is a number of heads of fields, heads of sections in disaster management agencies in the district of Lima Puluh Kota. The results of the study indicate that there have been mitigation actions from the BPBD district of Lima puluh kota